Stability of RNA structural motifs and its influence on editing efficiency by adenosine deaminases. (28th January 2010) - Phan, Vinhthuy; Thomas, Allen; Malasri, Kriangsiri; Sutter, Carrie Hayes
We propose a novel method to estimate editing efficiency by adenosine deaminases that act on RNA (ADARs). The method employs the notion of stability of secondary structure in the vicinity of edited sites during transcription. Such an analysis of 'dynamic' structural motifs of RNA is important because as a pre-spliced RNA is being transcribed and elongated, its entire structure, and thus its local structures, may change drastically. Our simulation showed that the stability of structures in the vicinity of edited sites correlates moderately highly with editing efficiency of edited sites recently established in laboratory experiments.